2021
DOI: 10.15517/am.v32i2.42066
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of the water status of rice inoculated with arbuscular mycorrhizae and with water deficit

Abstract: Introduction. The water deficit negatively affects rice plants and limits their productivity. Arbuscular mycorrhizal symbiosis has been shown to improve rice productivity in drought conditions. Objective. To propose a new categorization for the state of water stress of rice plants inoculated (AM) or not with arbuscular mycorrhizal fungi (nonAM) and exposed to water deficit (D) during the vegetative phase. Materials and methods. The experiment was carried out under controlled greenhouse conditions during the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreira et al 51 found that coffee plants inoculated with R. clarus had a higher mycorrhizal colonization (39%) and root dry matter than noninoculated plants, in soils at 71% of field capacity. Inoculation with AMF of different species has also been shown to potentially mitigate the effects of drought stress and increase resistance in bean 52 , rice 53 , tomato 54 , wheat 55 , and in orange 15 and apple 56 trees.…”
Section: Discussionmentioning
confidence: 99%
“…Moreira et al 51 found that coffee plants inoculated with R. clarus had a higher mycorrhizal colonization (39%) and root dry matter than noninoculated plants, in soils at 71% of field capacity. Inoculation with AMF of different species has also been shown to potentially mitigate the effects of drought stress and increase resistance in bean 52 , rice 53 , tomato 54 , wheat 55 , and in orange 15 and apple 56 trees.…”
Section: Discussionmentioning
confidence: 99%